PELAYANAN KESEHATAN PADA ANAK TUKANG “SUUN” DI YAYASAN LENTERA ANAK BALI KOTA DENPASAR - I Gede Yudiana Putra; Ni Putu Eka Febianingsih; I Kadek Agus Dwijaputra (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2022)
Background: Unfortunate Children such as street children in Denpasar must work to survive. One of the jobs they can do were to become hawkers and become a "tukang suun" in several markets in the Denpasar. This child received less attention, including health. The purpose of this activity is to provide health services and health education for street children, especially hawkers and "tukang suun" at the Bali Children's Lentera Foundation (LAB), Denpasar City. Method: This is a Community Services activity in with health services for 23 street children / "tukang suun" at the Bali Children's Lentera Foundation (LAB) Denpasar. This health service activity about weight and height measurements to find out nutritional status based on body mass index (BMI); hemoglobin levels examination, health education about clean and healthy behavior; and supplementary feeding. Results: Most of the children present were girls (74%) and most  were 4 - 9 years old. Based on body mass index (BMI), children’s were thin (50% in 4-6 years old and 37.5% in 7-9 years old). The results of hemoglobin levels examination through periphery blood tests, there were 89% of children have normal hemoglobin levels. Conclusion: based on BMI, street children / "tukang suun" tend to be thin but most have normal hemoglobin levels